Feasibility and Safety of Single-Incision Laparoscopic Surgery in Gastric Benign and Malignant Diseases - Kong Jing; Wu Shuo-dong; Fan Ying; Wang Yu (Gastroenterology Research and Practice)
We systematically searched Medline and Cochrane Library and the related references occurred in the citations until February 2013 and included all the cases who suffered from gastric benign and malignant diseases where single incision laparoscopic surgery was performed. A total of 69 cases with gastric diseases undergoing SILS surgery were reviewed to evaluate the feasibility, safety, and potential benefits of SILS for the gastric diseases. Demographic data, morphologic characterisation of the lesion, and perioperative parameters were analyzed retrospectively. The initial experience with SILS for benign gastric diseases and early gastric cancer showed that it is feasible and safe when performed by experienced laparoscopic surgeons. Despite the limited number and technical difficulties it can be proposed in selected patients.